PENGARUH DESAIN KEMASAN DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA KONSUMEN OSAMU COFFEE PONTIANAK - Domila, Antonius Iiq Pribadi; Syahrudin, Husni; Syamsuri, Syamsuri (Universitas Tanjungpura, 2026)
The aim of this research is to determine the influence of packaging design and brand image on purchasing decisions of consumers at Osamu Coffee Pontianak. This study involves three variables, namely packaging design (X1), brand image (X2), and purchasing decision (Y). The research method used is a quantitative approach with a causal associative design to examine cause-and-effect relationships. The data source consists of 93 consumers of Osamu Coffee Pontianak, and data were collected through the distribution of structured questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 26. The results indicate that packaging design does not have a significant effect on purchasing decisions, as shown by a significance value of 0.189 > 0.05 and a t-count of 1.324 < t-table of 1.986. Meanwhile, brand image has a positive and significant influence on purchasing decisions, with a significance value of 0.000 < 0.05 and a t-count of 3.835 > t-table of 1.986. Simultaneously, packaging design and brand image have a significant influence on purchasing decisions, indicated by a significance value of 0.000 < 0.05 and an f-count of 24.356 > f-table of 3.10.